2021
DOI: 10.1177/02646196211055924
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blindness and its major causes in sub-Saharan Africa in 2020: A systematic review and meta-analysis

Abstract: Background: Global studies show that the prevalence of visual impairment and blindness continued to rise despite the implementation of strategies outlined in the Global Action Plan, aimed at reducing these by the year 2020. Vision impairment impacts negatively on one’s independence, opportunities, and quality of life. Therefore, knowledge of the prevalence, and the major causes of blindness impairment in any population, is vital in designing strategies to address this public health challenge. Methods: Literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“… *Includes transportation (n = 4 ), fear of surgery (n = 3 ), able to perform daily activities with the condition (n = 2 ), and taking traditional medicine (n = 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… *Includes transportation (n = 4 ), fear of surgery (n = 3 ), able to perform daily activities with the condition (n = 2 ), and taking traditional medicine (n = 2). …”
Section: Resultsmentioning
confidence: 99%
“…3 A systematic review showed that cataract is a public health problem in Sub-Saharan Africa, accounting for more than 46% of cases of blindness. 4 In Ethiopia, cataract is the main cause of blindness and low vision, contributing to 49.9% of blindness and 42.3% of low vision cases. 5 Community and institutionally based studies conducted in Ethiopia have revealed that the prevalence of cataract ranges from 9.7% to 57%.…”
Section: Introductionmentioning
confidence: 99%
“…Its pooled prevalence (19.55%) (95% CI: 13.38%-25.72%) was higher than that in Brazil (6.3%), and sub-Saharan Africa (10%), but lower than in the SNNPR (35.7%) and Oromia regions (20.2%) in Ethiopia. [29][30][31] Variations in occurrence and water access can be attributed to socioeconomic development, awareness, socio-cultural factors, education, and local conditions. Understanding the impact of water supply, sanitation, and facial hygiene is crucial for policy reform and provides insights for combating trachoma in affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…• Social and Economic Impact: The African continent is one of the regions in the world with the most illiterate people [22]. A disturbing study of the high prevalence of vision impairment in East and West African countries was showed in [23]. ASR systems could then bring a huge social and economic benefits to these communities by allowing technologies that could considerably help them in their daily lives.…”
Section: Language Choices and Datasetsmentioning
confidence: 99%